Smart Building Demand Side Management Using Multi-Objective Archimedes Optimization Algorithms - El-Afifi, Magda I.; Sedhom, Bishoy E.; Eladl, Abdelfattah A. (2023 24th International Middle East Power System Conference (MEPCON), 2023)
This study presents an intelligent house energy management system that uses demand-side management load shifting to improve energy usage. This system optimizes home appliance management to moderate load demand, reducing power costs and peak-to-average ratio while prioritizing user comfort. Day-ahead and real-time load scheduling meet power customers' demands. Multi-objective Archimedes optimization techniques help distribute workload evenly across ON-peak and Off-peak hours and provide a fitness criterion. Additionally, home appliance coordination for real-time rescheduling is being proposed. Due to its similarities, the real-time rescheduling problem is called a knapsack problem and is solved using dynamic programming. This study also tests the proposed methodology in real-time pricing. Simulation results with a 95% confidence interval demonstrate the significance of the proposed optimization technique.